Improving Civics Learning Achievement Through Giving Initial Assignments in State High Schools - Mustapa T (JED (Jurnal Etika Demokrasi), 2021)
This research is related to improving students' learning achievement by giving beginning tasks before the material is presented at citizen lesson at grade X SMA Negeri 4 Polewali academic year 2019-2020. The population of this research are the students of four classes, with 144 students. At the same time, the sample consists of two classes with 72 students. This sample divided into two groups, namely the control group and experiment one. The method of this research is an experiment by using t-test data analysis technique. This research shows that the student's learning achievement was taught by giving the Initial Assignments with the mean score 7.81 while the students' learning achievement without Initial Assignments 7.07. It means that the student's learning achievement by giving Initial Assignments is higher than the students' learning achievement without initial Assignments.Penelitian ini berkaitan dengan peningkatan prestasi belajar siswa dengan memberikan tugas awal sebelum materi disampaikan pada pelajaran warga kelas X SMA Negeri 4 Polewali tahun ajaran 2019-2020. Populasi dalam penelitian ini adalah siswa dari empat kelas yang berjumlah 144 siswa. Sedangkan sampel terdiri dari dua kelas dengan 72 siswa. Sampel ini dibagi menjadi dua kelompok, yaitu kelompok kontrol dan kelompok eksperimen. Metode penelitian ini adalah eksperimen dengan menggunakan teknik analisis data uji-t. Hasil penelitian menunjukkan bahwa prestasi belajar siswa diajar dengan pemberian Tugas Awal dengan nilai rata-rata 7,81 sedangkan prestasi belajar siswa tanpa Tugas Awal 7,07. Artinya prestasi belajar siswa dengan pemberian Tugas Awal lebih tinggi daripada prestasi belajar siswa tanpa Pemberian Tugas Awal.